Use of angiotensin receptor – neprilysin inhibitors in heart failure: a paradigm shift - M. O.E. Irhuma (AOSIS, 2016)
Heart failure is a clinical syndrome responsible for at least one-third of hospitalisations amongst cardiac patients, with escalating mortality and healthcare costs on both public and private health care. Both prevalence and incidence of heart failure increase steeply with advancing age, making it a growing public health problem. Pathophysiologically, heart failure clinically presents in two common forms: heart failure with preserved ejection fraction and heart failure with reduced ejection fraction. The cornerstone of heart failure management includes the use of angiotensin-converting enzyme inhibitors. A recently developed pharmacotherapy that inhibits both the angiotensin receptor and the enzyme neprilysin has shown promise in the management of heart failure with reduced ejection fraction. This article will highlight the impact of this new therapy and its potential use in heart failure with reduced ejection fraction.